2011
DOI: 10.1080/14616696.2010.540351
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Education Across European Countries and Cohorts

Abstract: This article investigates the intergenerational transmission of education in 28 European countries. The main aim is to answer the following questions: (1) To what degree are parents' education and the educational attainment of their children related in different countries and cohorts, and (2) how can we explain the country-cohort variation in these effects by looking at contextual characteristics? In order to explain this variation, we focus on the degree of industrialisation, female labour force participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…The same finding has been produced by comparative research restricted to tertiary education (Arum et al 2007). A recent comparative study also finds a negative relationship between IOE, measured in absolute terms, and the level of industrialisation and expenditure in education (Van Doorn et al 2011). It is thus possible to say that, contrary to the results of previous comparative research (Shavit and Blossfeld 1993), the available evidence points to a decline in IOE (Breen et al 2009;Ballarino et al 2009).…”
Section: Inequality Of Educational Opportunities and Educational Retumentioning
confidence: 69%
“…The same finding has been produced by comparative research restricted to tertiary education (Arum et al 2007). A recent comparative study also finds a negative relationship between IOE, measured in absolute terms, and the level of industrialisation and expenditure in education (Van Doorn et al 2011). It is thus possible to say that, contrary to the results of previous comparative research (Shavit and Blossfeld 1993), the available evidence points to a decline in IOE (Breen et al 2009;Ballarino et al 2009).…”
Section: Inequality Of Educational Opportunities and Educational Retumentioning
confidence: 69%
“…However, the twin models that we present do not give insights into which family background factors are important for both education and age at first birth. Previous investigations have pointed to SES of the parents (van Doorn et al 2011) andparental demographic behavior (e.g., Lappegård andRønsen 2005;Marini 1985;Nisén and Myrskylä 2014;Rijken and Liefbroer 2009). Recent investigations also show that social ties, such as friends (Balbo and Barban 2014), influence fertility timing and that siblings influence each other (Lyngstad and Prskawetz 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, research has also cast doubt on the idea of a causal effect of education on the age at first birth, suggesting that family background characteristics (social and/or genetic factors) cause spurious associations between educational attainment and fertility timing of women (Neiss et al 2002;Rodgers et al 2008). Social stratification research has indicated considerable similarity between parents, children and siblings in education and socioeconomic attainment (Branigan et al 2013;van Doorn et al 2011) and in fertility behavior (Murphy 1999;Rijken and Liefbroer 2009). The similarity/intergenerational transmission may be due to parental socioeconomic resources and/or socialization processes (Nisén and Myrskylä 2014;Rijken and Liefbroer 2009) but also to shared genetic dispositions given the sufficient evidence for a genetic component for both outcomes (Branigan et al 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…Across countries, parental education is the strongest determinant of educational success (Van Doorn et al 2011). Personal characteristics, like migration background and health, are relevant for educational attainment, too.…”
Section: What Determines Educational Successmentioning
confidence: 99%